ASTI global update 2020 - Beintema, Nienke M.; Nin-Pratt, Alejandro; Stads, Gert-Jan (International Food Policy Research Institute, 2020)
This note provides an overview of investment trends in global agricultural research to the year 2016, which revises ASTI’s prior global update (Beintema et al. 2012). Although data on agricultural research investments are outdated, irregular, or incomplete for some countries, this update was prompted by ASTI’s new datasets for Africa and Asia, newly released data for high-income countries from the Organisation for Economic Cooperation and Development, and additional data from various other secondary sources, particularly for Latin America, China, and United States.